The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/ijerph18179369
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Health Risk Assessments of an Abandoned Gold Mine (Remance, Panama): Complex Scenarios Need a Combination of Indices

Abstract: The derelict Remance gold mine is a possible source of pollution with potentially toxic elements (PTEs). In the study area, diverse mine waste has been left behind and exposed to weather conditions, and poses risks for soil, plants and water bodies, and also for the health of local inhabitants. This study sought to perform an ecological and health risk assessment of derelict gold mining areas with incomplete remediation, including: (i) characterizing the geochemical distribution of PTEs; (ii) assessing ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 43 publications
1
29
0
2
Order By: Relevance
“…The probabilistic risk assessment revealed that 100% of the consumers of local crops might be exposed to carcinogenic and non-carcinogenic health effects caused by the ingestion of food contaminated with trace elements. Similar findings were reported in mining areas of Panamá (González-Valoys et al, 2021), Peru (Orellana Mendoza et al, 2021, and Central China (Li et al, 2018a(Li et al, , 2018b, where the presence of potentially toxic elements in edible plants exceeded the safe exposure limit for non-carcinogenic and carcinogenic risk related to crop ingestion.…”
Section: Human Health Risksupporting
confidence: 80%
See 1 more Smart Citation
“…The probabilistic risk assessment revealed that 100% of the consumers of local crops might be exposed to carcinogenic and non-carcinogenic health effects caused by the ingestion of food contaminated with trace elements. Similar findings were reported in mining areas of Panamá (González-Valoys et al, 2021), Peru (Orellana Mendoza et al, 2021, and Central China (Li et al, 2018a(Li et al, , 2018b, where the presence of potentially toxic elements in edible plants exceeded the safe exposure limit for non-carcinogenic and carcinogenic risk related to crop ingestion.…”
Section: Human Health Risksupporting
confidence: 80%
“…Trace elements can appear in agricultural soils naturally (i.e., atmospheric deposition, weathering, parent rock, or erosion) as well as through anthropogenic activities developed in the vicinity of these soils and by the same agricultural practices that incorporate various contaminants into the soil (Kumar et al, 2022). Among anthropogenic activities, mining is considered an important source of trace elements pollution since, when not carried out properly, it can release potentially toxic elements into the surrounding environment (González-Valoys et al, 2021;Jiménez-Oyola et al, 2021a, 2021bWang et al, 2019aWang et al, , 2019bWang et al, , 2019cXu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal pollution in soil is closely related to human activities during mining in open-pit mines [ 14 , 15 , 16 ]. For example, heavy metals spread far and wide through dust and wind effects from various human activities, migrate to nearby water bodies and soils, and destroy the local ecological environment [ 17 , 18 ]. They subsequently enter the human body in various ways, such as plant absorption, human skin contact and inhalation [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A homogenised soil sample (1.5 g) was placed inside a test tube and mixed with 1.5 mL of deionised water, 0.015 g of CaCO 3 and 0.250 mL of TTC (3% v/w) to be vortexed (2 min) and incubated (Memmert In 30) at 37 • C for 24 h. Afterwards, samples were vortexed using methanol as an extractant agent and tubes were centrifuged (Ortoalresa, Unicen 21) at 4000 rpm for 10 min. The supernatant was analysed in a UV-visible spectrophotometer at 485 nm (Gonzalez-Valoys et al, 2021). Data were expressed as μg TPF g soil…”
Section: Sb Mobility and Enzymatic Activitymentioning
confidence: 99%